Majątki szlacheckie współczesnej gminy Świdnica w okresie habsburskim (1526-1740) = Świdnica's gentry estate in the Habsburg period (1526-1740) - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the period of 1526-1740, Świdnica's administrative territary (in its modern sense) comprised gentry estate that was part of the duchies of present-day Głogów and Krosno. It was not a homogenous area since the duchies belonged to different dynasties and, consequently, were under different fealties, the Czech Kingdom (Silesia) and Brandenburg, which was reflected in their administrative division: Drzonów, Lipno, Grabowiec, Koźla and Piaski were a group of estates that had been separared from the duchy of Głogów and given to Brandenburg margraves in 1482 and so became part of the duchy of Krosno, while Radomia, Słone, Buchałów, Letnica, Dobra (non-existent now), Świdnica and Wilkanowo belonged to the duchy of Głogów - being part of Silesia - and so they remained an integraf part of Grünberg (Zielona Góra) weichbild.
Keywords: Świdnica (woj. lubuskie, pow. zielonogórski, gm. Świdnica); Świdnica - historia; majątki szlacheckie; szlachta śląska; 16-18 w.